Analisis Penerjemahan Kalimat Pasif Bahasa Inggris Ke dalam Bahasa Indonesia pada Novel Morning, Noon and Night Karya Sidney Sheldon - Suprato, Djuria (Bina Nusantara University, 2013)
A translated novel can enrich the culture and life of other nations. In order to properly understand the intended meaning of the author, the translator must understand both the source language and the target language. Meaning is an important element in the translation. Article explained the results of the study of the passive sentences of the source language (English) translated into Indonesian. The results of the study show that not all of the passive sentences of the source language can be translated in the form of passive sentences in target language. Instead, the passive sentences can be translated in the form of active sentences because of the meaning contained.